2002
DOI: 10.2307/3072016
|View full text |Cite
|
Sign up to set email alerts
|

Germination Ecology of Neotropical Pioneers: Interacting Effects of Environmental Conditions and Seed Size

Abstract: Abstract. Germination provides many potentially unrecognized sources of variation in the regeneration niche. In this study we relate germination requirements and seed size for 16 species of pioneer trees to microclimatic conditions present in gaps in semi-deciduous rain forest in Panama. We found that, whereas increased duration of direct irradiance can be an effective indicator of the presence of a canopy gap across all scales of canopy openness, diel fluctuations in soil temperature effectively discriminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
112
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(125 citation statements)
references
References 26 publications
(37 reference statements)
8
112
0
5
Order By: Relevance
“…Although seed size effects on drought sensitivity were not detected in this study, a comparable field experiment that tracked both the emergence and the initial survival of pioneer seedlings at the same study site found lower survivorship of small-seeded species (Dalling and Hubbell 2002). We suggest that drought might contribute to such size-dependent seedling mortality in pioneer seedlings, since the maximum soil depth from which successful seedling emergence can take place is strongly correlated with seed mass (Bond et al 1999;Pearson et al 2002). Consequently, the very smallest-seeded pioneers such as M. argentea (0.063 mg) are only able to emerge through a few millimeters of soil (Pearson et al 2002), which exhibit the most severe drought conditions.…”
Section: Drought In Tropical Forestsmentioning
confidence: 78%
See 3 more Smart Citations
“…Although seed size effects on drought sensitivity were not detected in this study, a comparable field experiment that tracked both the emergence and the initial survival of pioneer seedlings at the same study site found lower survivorship of small-seeded species (Dalling and Hubbell 2002). We suggest that drought might contribute to such size-dependent seedling mortality in pioneer seedlings, since the maximum soil depth from which successful seedling emergence can take place is strongly correlated with seed mass (Bond et al 1999;Pearson et al 2002). Consequently, the very smallest-seeded pioneers such as M. argentea (0.063 mg) are only able to emerge through a few millimeters of soil (Pearson et al 2002), which exhibit the most severe drought conditions.…”
Section: Drought In Tropical Forestsmentioning
confidence: 78%
“…We suggest that drought might contribute to such size-dependent seedling mortality in pioneer seedlings, since the maximum soil depth from which successful seedling emergence can take place is strongly correlated with seed mass (Bond et al 1999;Pearson et al 2002). Consequently, the very smallest-seeded pioneers such as M. argentea (0.063 mg) are only able to emerge through a few millimeters of soil (Pearson et al 2002), which exhibit the most severe drought conditions. Such seedlings are therefore likely to be more vulnerable to drought and to remain susceptible for a longer period post-emergence relative to larger seeded species.…”
Section: Drought In Tropical Forestsmentioning
confidence: 99%
See 2 more Smart Citations
“…Small-seeded species (< 1 mg seed mass) are frequently removed by litter ants at the soil surface , are susceptible to fungal pathogens (Dalling et al 1998), and are only capable of successfully emerging from the surface few millimetres of soil (Pearson et al 2002). Seed relocation by litter-dwelling ants in the forest understorey may increase chances of seedling recruitment for pioneer species since microsites suitable for germination and establishment are often patchy and scarce.…”
Section: Introductionmentioning
confidence: 99%